PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KOMPETENSI PEGAWAI PADA KANTOR REGIONAL VI BADAN KEPEGAWAIAN NEGARA MEDAN - Siti Mujiatun (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
Data collection techniques in this study was a questionnaire (Questionnaire), interview (interview) . study  analysis technique used is a simple correlation, t test, and test determinant, multiple correlation and F test Training significantly influence employee competence Regional Office VI State Personnel Board Medan.Motivation work significantly influence employee competence Regional Office VI State Personnel Board Medan. Work motivation significantly influence employee competence Regional Office VI Medan State Personnel Board.Keyword : Training, work motivation, competency